Estudo da tecnologia de filtração por osmose reversa na purificação da água - Bezerra, Anderson Gomes (Universidade Federal Rural do Semi-Árido, 2018)
In recent years, at the international level, membrane desalination systems, more specifically reverse osmosis has been gaining a lot of evidence as an extremely effective method to carry out water purification. It is currently the most widely used method for this purpose. This process is applied in several industrial sectors, and also to perform the desalination of water containing high levels of dissolved salts, to obtain ultrapure water for consumption. One of the advantages of reverse osmosis in relation to other water treatment technologies is due to its simple mechanism of operation. Brazil, despite being a privileged country in natural resources and possessing an immense amount of water reserves, there are regions that suffer greatly from the problem of water scarcity. The objective of this work is to present the fundamental aspects regarding reverse osmosis water filtration technology through a bibliographical research addressing the main technologies behind such systems, such as the materials used for the production of filtration membranes and the configurations of treatment, addressing the basic principles of operation of each one of them.
Monografia
Keywords: Osmose reversa; Membranas; Filtração; Dessalinização; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA